Identification of an endo-1,4-beta-xylanase of Ustilago maydis - Geiser, Elena (BioMed Central, 2013)
BACKGROUND: The utilization of raw biomass components such as cellulose or hemicellulose for the production of valuable chemicals has attracted considerable research interest in recent years. One promising approach is the application of microorganisms that naturally convert biomass constituents into value added chemicals. One of these organisms – Ustilago maydis – can grow on xylan, the second most abundant polysaccharide in nature, while at the same time it produces chemicals of biotechnological interest. RESULTS: In this study, we present the identification of an endo-1,4-beta xylanase responsible for xylan degradation. Xylanase activity of U. maydis cells was indirectly detected by the quantification of released reducing sugars and could be confirmed by visualizing oligosaccharides as degradation products of xylan by thin layer chromatography. A putative endo-1,4-beta-xylanase, encoded by um06350.1, was identified in the supernatant of xylan-grown cells. To confirm the activity, we displayed the putative xylanase on the surface of the xylanase negative Saccharomyces cerevisiae EBY100. The presented enzyme converted xylan to xylotriose, similar to the source organism U. maydis. CONCLUSIONS: The xylan degradation ability together with its unicellular and yeast-like growth makes U. maydis MB215 a promising candidate for the production of valuable chemicals such as itaconic acid or glycolipids from lignocellulosic biomass. Therefore, the characterization of the endo-1,4-beta-xylanase, encoded by um06350.1, is a further step towards the biotechnological application of U. maydis and its enzymes.